2001
DOI: 10.1016/s0002-9270(01)03896-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality of health care in inflammatory bowel disease: development of a reliable questionnaire (QUOTE-IBD) and first results

Abstract: A short, valid, reliable questionnaire was developed to measure the opinions of patients with inflammatory bowel disease on quality of health care. The QUOTE-IBD can be used for identification of areas for improvement, with the aim of optimizing health care in inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 0 publications
1
63
2
1
Order By: Relevance
“…In an effort to integrate ‘patient values’, a recently published study carried out by the European Collaborative Study Group on IBD (EC-IBD) reported the development of a questionnaire to measure ‘quality of care through the patient’s eyes for IBD patients’ (QUOTE-IBD) in national and international surveys [6]. It consists of 23 questions, 10 generic and 13 disease-specific.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to integrate ‘patient values’, a recently published study carried out by the European Collaborative Study Group on IBD (EC-IBD) reported the development of a questionnaire to measure ‘quality of care through the patient’s eyes for IBD patients’ (QUOTE-IBD) in national and international surveys [6]. It consists of 23 questions, 10 generic and 13 disease-specific.…”
Section: Introductionmentioning
confidence: 99%
“…The QUOTE instrument for persons with IBD, the QUOTE-IBD, includes 10 generic questions and 13 disease specific questions. The questionnaire comprises three categories: Importance, the weight that the patient gives to various care aspects; Performance, experiences regarding the function of medical practices and healthcare professionals for each aspect of care; and Quality Impact, the combined effect of importance and performance (85).…”
Section: Assessing Quality Of Carementioning
confidence: 99%
“…Some studies have been performed on the aspect of quality of care among patients with IBD showing that patients gave relatively poor marks to parts, such as being provided with information and the psychological as well as physical approach (85)(86)(87). The existing knowledge about IBD and quality of care is based on studies measuring quality of care with predefined questions (86,88).…”
Section: Assessing Quality Of Carementioning
confidence: 99%
See 2 more Smart Citations